KONTRIBUSI PEREMPUAN NELAYAN TERHADAP KETAHANAN PANGAN DAN EKONOMI KELUARGA DI PETUK KATIMPUN - Muhammad Zusanri Batubara; Atem Atem; M. Syaeful Anam; Yonatan Ari Santoso; Muhamad Risky Hidayat; Aprilia Lusiana (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
Fishing is widely practised by women in Petuk Katimpun. This indicates that women have dual roles in their lives. This study aims to examine the activities of women fishing in peat swamps and analyse the roles, functions, and objectives of women as fishermen. The author argues that women fishermen have the capacity and dual roles in their livelihoods to achieve food security and support family economies. An ethnographic approach was used as the research method among women fishermen in Petuk Katimpun. Data collection was carried out through participatory observation, in-depth interviews, and literature studies and analysed using descriptive analysis techniques. The findings show that women make a significant contribution to food security and the family economy. The role of women fishers is not limited to household activities. Still, it encompasses a comprehensive range of tasks, from preparing fishing gear and setting nets or traps to hauling in the catch, sorting the fish, and marketing the catch. The purpose of women working as fishermen is closely related to efforts to secure the family's future, ease the burden on their husbands, and ensure that the needs of large families are met sustainably. Women's income is significant because their husbands' income as fishermen is often uncertain, depending on weather conditions, fishing seasons, and the availability of fishery resources. Women's involvement in the fishing profession and other activities significantly improves family welfare, thereby contributing to food security and family economic resilience. The presence of women fishers is an essential pillar in developing a more inclusive, empowered, and sustainable river community.